Analysis of the Effectiveness and Efficiency of the Implementation of the Sawahlunto City Revenue and Expenditure Budget - Berta Agus Petra; Yosi Puspita Sari (UPI YPTK Journal of Business and Economics, 2022)
This study aims to analyze the effectiveness and efficiency of the revenue and expenditure budget of Sawahlunto City. The object of this research is the Regional Financial and Asset Management Agency (BPKAD) of Sawahlunto City. The data used in this study are financial reports compiled by BPKAD Sawahlunto City for 5 years (2016-2020). From this study, it was found that the effectiveness of the implementation of the Sawahlunto City Regional Revenue and Expenditure Budget in 2016-2020 is quite effective, because the level of effectiveness is still in the rank of 99%. Meanwhile, for the level of efficiency, it can be concluded that the city of Sawahlunto is quite efficient, because the percentage is still below 100%.